Improvement of the self-management mechanism of science-technology based organizations. Case study of R&D organizations operated by State budget - Hoa, Tran Ngoc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT)
The self-management in science-technology (S&T) activities has been applied in Vietnam since early time. The practical organization of self-management, however, remains to show many shortages. This study is focused on analysis of successes and shortcomings observed in implementation of self-management of S&T organizations through the case of the ones operated by the State budget and experiences of implementation of the mechanism in some advanced countries. The analysis would be the background to propose a set of solutions for improvement of the institutional self-management of S&T based organizations and R&D organizations in purpose to enhance the effectiveness of activities of these organizations and to contribute to improving the system of legal documents for S&T activities in Vietnam. Code: 13012501